Recommendations to POSHAN Abhiyaan, India’s national nutrition mission on issues to consider in strengthening efforts to improve data availability and data use in the context of POSHAN Abhiyaan - CGIAR Research Program on Agriculture for Nutrition and Health (2021)
The report was finalized in December 2020 and made available online in January 2021. It was developed by IFPRI researchers, NITI Aayog, and IDinsight. An accompanying policy note provides a shorter summary of the report and was also made available online.